Analisis Kebutuhan Pembangunan Fasilitas Pada Bidang Kesehatan di Provinsi Kalimantan Selatan Menggunakan Waqaf dengan Metode ANP - Yassir Fahmi, Muhammad; Sadewa, Manik Mutiara (P3M Politeknik Negeri Banjarmasin, 2022)
To determine the use of waqf assets, nazhir or waqf institutions need to conduct a needs analysis so that the waqf property is truly beneficial to the community (mawquf 'alaih). Development in the health sector is one of the uses of waqf assets. This study aims to find the priority needs for facility development in the health sector in South Kalimantan Province using waqf assets using the ANP (Analytical Network Process) method based on the opinions of nazhir, wakif, government and academics. Based on the results of the study, it can be concluded that the construction of health care facilities is a priority need in South Kalimantan Province in an effort to improve the quality of public health, while clinics are the most important criteria in the construction of health service facilities in this province using waqf assets.